Genetic and morphological analysis of complex Giuris group species from Limboto Lake, Gorontalo Province, Indonesia - ARAFIK LAMADI; AKHSAN FIKRILLAH PARICAHYA; FENI IRANAWATI; MAHENO SRI WIDODO; DEWA GEDE RAKA WIADNYA (Society for Indonesian Biodiversity, 2023)
Abstract. Lamadi A, Paricahya AF, Iranawati F, Widodo MS, Wiadnya DGR. 2023. Genetic and morphological analysis of complex Giuris group species from Limboto Lake, Gorontalo Province, Indonesia. Biodiversitas 24: 5223-5233. Wallacea, especially Sulawesi, has a high endemism level with genuine biodiversity for mammals, reptiles, freshwater, and brackish fishes. Fish biodiversity in Limboto Lake, a great natural lake of Gorontalo Province, Indonesia, still needs to be scientifically explored, in contrast with its utilization for human activities that have anthropogenic effects on their ecosystem. Eleotridae is a taxonomical complex to their identification and distributed well in Sulawesi, including Limboto Lake with genus Giuris, known locally as hulu'u fish. Ambiguous identification in Giuris margaritaceus morphologically causing misidentification in molecular analysis, including using Cytochrome Oxidase subunit I (COI) region's information. Giuris specimens from Limboto Lake were collected from June 2022 until May 2023. From 662 individuals, length and weight relationship analysis results showed the population is mildly positive allometric (W= 0.11TL3.08). Meristic measurement result (D1 VI; D2 I.8-9; A I.9; P 14-16; V I.5; C 13-14) directing to G. margaritaceus with several small differences. COI analysis using six random specimens of the Limboto Lake population, comparing with four population from NCBI and BOLD System identified as G. margaritaceus or its synonym Ophieleotris aporos, indicating all populations is separated species from one another with P-distances more than 2% and made separated groups in phylogenetic tree and haplotype network. Misidentification issues in the Giuris margaritaceus taxonomical name for all five populations indicate they're potentially separated into five different species, with or without including Giuris margaritaceus, and potentially from currently described species or being new species in the future. Limboto Lake population made three haplotypes with high haplotype diversity (0.733) and low nucleotide diversity (0.001), indicating this population is facing high stressors and starting to grow. Understanding Giuris ambiguities could help governments, researchers, conservationists, and other stakeholders to mapping the ecological priorities.